Layanan Edukasi Bagi Ibu Dalam Upaya Mencegah Covid-19 Pada Anak: Educational Services for Mothers in Effort to Prevent Covid-19 in Children - Wahyu Ersila; Lia Dwi Prafitri; Windha Widyastuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The incidence of COVID-19 in children and toddlers in Indonesia is still under monitoring, especially when the government implemented a Face-to-Face Meeting for the first one in July 2021. The most significant percentage figures are shown in children aged 0-2 years, then the age group 3-6 years and 16-18 years. Transmission occurs due to direct patient contact, especially in adults who transmit it to children. It needs the role of parents, in this case, mothers, to be a pioneer for families to prevent COVID-19 in children. This service aims to increase the mother's knowledge about COVID-19 disease in children and prevent COVID-19 illness in children. Devotional methods are lectures, Q&A, and demonstrations. To find out the increase in expertise using pre-test knowledge test and post-test. The result was an increase in knowledge in mothers before the extension of maternal knowledge; on average, the value of 66.92, and after counseling, knowledge to 86.15. It is necessary to do similar activities to continue to increase maternal expertise so that the degree of health increases and the number of COVID-19 spread decreases.